ADAPTATION STRATEGIES TO HUMAN PHYSIOLOGICAL DISCOMFORT AMONG ELDERLY PEOPLE IN KATSINA URBAN, KATSINA STATE, NIGERIA - NATA'ALA, S.M; SALEH, H; HASHIDU, U.S (FUDMA Journal of Earth and Environmental Sciences, 2024)
Information on adaptation strategies to human physiological discomfort is very important for individuals, groups of people, planners, and policymakers in the world's tropical regions where thermal stress poses a significant threat to life, especially among elderly people. Based on this, the aim of the study, therefore, is to assess adaptation strategies to human physiological discomfort among elderly people due to temperature and humidity extremes in residential areas and workplaces during the hot and cold seasons in Katsina. A total of 100 copies of a questionnaire were administered to the elderly people to obtain information on their adaptation strategies. A stratified random sampling method was used to select the respondents in the study area. Descriptive statistics were then used to describe their perception of adaptation strategies to human physiological discomfort. Results obtained revealed that in the hot season, the majority of the respondents at residence areas and working places perceived outdoor and indoor with fans "respectively" as their best-adapting strategies to human physiological discomfort due to temperature and humidity extremes. However, in the cold season, the study revealed that the majority of the respondents in residence areas and workplaces perceived thick dress as their best-adapting strategy for human physiological discomfort due to temperature and humidity extremes. Adapting strategies to human physiological discomfort depends primarily not only on environmental conditions but relaxing in natural environments and using customized clothing materials. People are encouraged to continue planting trees in and around their homes, working workplaces and to adequately prepare to adapt to extreme hot and cold seasons.